PENGARUH DIRECT MARKETING DAN KUALITASPRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN VARIABEL INTERVENING KEPUASAN KONSUMEN PADA LIVE STREAMING MARKETING TIKTOK: (Studi Kasus : Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Katolik Santo Thomas) - Simanihuruk, Peran; Sidabutar, Ruth Natalia D. Roitona; Tamba, Darwis; Tarigan, Immanuael; Sagala, Roslinda (Jurnal Manajemen dan Bisnis, 2023)
This study aims to analyze the effect of direct marketing and product quality on purchasing decisions with the intervening variable of consumer satisfaction in live streaming marketing on Tiktok. The population is all students of the Faculty of Economics and Business, Catholic University of Santo Thomas Medan. The research sample was 96 students. Data collection techniques, questionnaires and documentation, data analysis techniques, path analysis, to prove the hypothesis used the t test and F test while to see the closeness of the relationship seen from the correlation coefficient and to find out how much the independent variable can explain the dependent variable seen from the coefficient of determination. The results of the path analysis equation Y = 0.372X1 + 0.538X2 means that direct marketing and product quality have a positive and significant effect on purchasing decisions. The path analysis equation for the influence of direct marketing and product quality on consumer satisfaction Z = 0.243X1+0.586X2 means that direct marketing and product quality have a positive and significant effect on customer satisfaction. The path analysis equation for the influence of direct marketing and product quality on purchasing decisions through customer satisfaction shows Z = 0.076X1+ 0.345X2 + 0.447Y, meaning that the direct marketing variable and product quality have a positive and significant effect on purchasing decisions through customer satisfaction. With the F test, direct marketing, product quality has a positive effect on purchasing decisions through consumer satisfaction on live tiktok (Fcount 56.850 > Ftable 2.70). Partially, it shows that direct marketing variables have a positive and significant effect on purchasing decisions on Tiktok Live where tcount is 4.882 > ttable 1.66140, product quality variables have a positive and significant effect on purchasing decisions on Tiktok Live where tcount is 7.062 > ttable 1.66140, direct marketing variables have an effect positive and significant to consumer satisfaction on tiktok live where tcount 2.764 > ttable 1.66140, product quality variables have a positive and significant effect on consumer satisfaction on tiktok live where tcount 6.679 > ttable 1.66140. The purchase decision variable has a positive and significant impact on consumer satisfaction on live tiktok where tcount is 4.043 > ttable 1.66159. The coefficient of determination (R²) is 0.650, meaning that consumer satisfaction can be explained by direct marketing, product quality and purchasing decisions by 65.0%, while 35% is explained by other factors not explained in this study.